MicroRNA-18b-5p Inhibits the Malignant Progression of Prostate Cancer Through Downregulating TRAF5 - Wang X; Yu X; Wang Y; Lian J; Li Z; Dong C; Song H; Zhang L; Zhang H; Wang Y (International Journal of General Medicine)
Xiaoran Wang,1 Xin Yu,2 Yong Wang,1 Jihu Lian,1 Zhenxiao Li,2 Chunli Dong,2 Haitao Song,2 Liangliang Zhang,2 Haitao Zhang,2 Yongjie Wang2 1Urology Surgery, The People Hospital of Jilin Province (Jilin Province Clinical Research Center of Emergency and Critical Diseases), Changchun, Jilin, 130021, People’s Republic of China; 2Intensive Care Unit, The People Hospital of Jilin Province (Jilin Province Clinical Research Center of Emergency and Critical Diseases), Changchun, Jilin, 130021, People’s Republic of ChinaCorrespondence: Yongjie Wang, Intensive Care Unit, The People Hospital of Jilin Province (Jilin Province Clinical Research Center of Emergency and Critical Diseases), 1183 Gongnong Road, Changchun, Jilin, 130021, People’s Republic of China, Tel +86-0431-85595089, Email Wangyongjie5918@163.comObjective: Extensive efforts have been made for translating the mechanisms of microRNAs (miRNAs) in prostate cancer (PCa). However, the specific role of miR-18b-5p in PCa is still in obscurity. Herein, miR-18b-5p/TRAF5 axis-oriented exploration in PCa has been launched.Methods: miR-18b-5p and TRAF5 expression in PCa tissues and cells was detected by RT-qPCR. In-vitro experiments were conducted to investigate the biological functions of miR-18b-5p and TRAF5 in PCa cells. The underlying mechanism of miR-18b-5p was revealed by luciferase reporter assay, miRNA Pull down, RT-qPCR, and rescue assay.Results: Lower miR-18b-5p and higher TRAF5 expression were observed in PCa tissues and cell lines. miR-18b-5p overexpression or TRAF5 downregulation impaired proliferation, diminished migratory and invasive properties, as well as advanced apoptosis in PCa cells. miR-18b-5p could regulate TRAF5 expression by directly binding to its 3′-untranslated region. Overexpression of TRAF5 abolished the suppressive effects of restored miR-18b-5p on PCa cell progression.Conclusion: This study elucidates that upregulated miR-18b-5p impedes PCa cell progression via downregulating TRAF5, which may provide a novel therapeutic basis for PCa. Keywords: prostate cancer, microRNA-18b-5p, TRAF5, proliferation, invasion, migration, apoptosis